Effects of oxygen and nitrogen gases on the dynamics between the interfaces of self-mated titanium pairs. (20th April 2016) - Chang, Yuh-Ping; Chou, Huann-Ming; Chu, Li-Ming; Wang, Jin-Chi
The chemical reactions of titanium in air include both TiO2 and TiN. The phenomena are quite complex, and the reaction mechanisms are still unclear. However, as titanium is in widespread use all over the world, it is important that the reaction mechanisms be thoroughly investigated. Therefore, in this study, the continuous variations in the electrical contact resistance and the friction coefficient are simultaneously measured to monitor the dynamics of self-mated titanium pairs in an air, O2 or N2 gas flow. When a large amount of TiO2 formed on the surface of the plate for Ti/Ti, the results showed the tribo-physical phenomena of higher electrical contact resistance, friction coefficient almost doubled and severe wear. When a large amount of TiN formed on the surface of the plate for Ti/Ti, the results showed the tribo-physical phenomena of lower electrical contact resistance, friction coefficient almost halved and mild wear with some lubrication. Therefore, variations in the electrical contact resistance can be applied to determine whether the chemical reaction on the surface was TiO2 or Ti with TiN. The unsymmetrical frictional models and wear mechanisms of the self-mated titanium pairs in the air, O2 or N2 gas flow were proposed.